The Women in Medicine Summit (WiMS): Engaging students to identify and address gender-associated challenges in medicine (Canadian Medical Education Journal, 2020)
The Women in Medicine Summit (WiMS) is a novel, student-led conference initiated at the University of Toronto to engage the medical community in a discussion about unique gender-distinctive challenges in medicine. We identified topics inadequately addressed in undergraduate curriculums, including techniques to address microaggressions and balance work-life commitments. Students from five Canadian medical schools attended WiMS in 2018. Attendees perceived significant improvement in readiness in identifying and resolving gender-associated issues following the conference. Our findings may be used to motivate curriculum development and adoption of similar initiatives to improve education on diversity.